Health-related quality of life in patients with common variable immunodeficiency switching from intravenous to subcutaneous immunoglobulin therapy - Mona Al-Ahmad; Ahmed Maher; Jasmina Nurkic (SpringerOpen, 2017)
Common variable immunodeficiency (CVID) is the most common symptomatic primary immunodeficiency disease (PID) among adults. CVID consists of two phenotypes - one in which infections are the characteristic and another in which impressive inflammatory and/or hematological complications also develop, including lymphadenopathy, splenomegaly, autoimmune cytopenias, enteropathy, and granulomatous disease. These phenotypes appear to be stable, are related to immunological and inflammatory markers, and are predictive of outcomes. Both subcutaneous immunoglobulin (SCIG) and intravenous immunoglobulin (IVIG) are equally effective for replacement therapy. No data are available about specific factors affecting the quality of life related to switching from IVIG to SCIG in the Arabian Gulf area. We present the case reports of three adult CVID patients, who were shifted from IVIG to SCIG by the US conversion method (1 : 1.5). We followed-up patients for clinical outcomes, side-effects, immunoglobulin G (IgG) trough levels, annual infection rate, and quality of life using questionnaires (RAND-36) over a 3-year period. Three patients (two females and one male), with a mean age of 26 years, had received IVIG [Gamunex-C (Grifols Therapeutics Inc., NC, 27709 USA) 10%; Grifols] treatment for an average duration of 4 years and had average IgG trough levels of 7.7±2.9 g/dl. Patients were shifted to SCIG [Subcuvia (Baxalta Innovation GmbH, Vienna, Austria) 10%; Baxter] for different reasons. SCIG was administered, using an infusion pump, under medical supervision at the hospital, on a weekly basis. The average IgG trough level on SCIG was 10.4±1.5 g/dl. The annual infection rate of pneumonias, sinusitis, otitis media, and others significantly declined after switching to SCIG in all three patients. However, while on IVIG treatment, some patients reported headache and malaise, but when on the SCIG treatment the reactions were mild and infusion site-related such as erythema, swelling, and itching. Remarkably, all patients were successfully switched to SCIG with significant decrease in the annual rate of infections and a favorable steady-state of serum trough levels of IgG. The use of SCIG was generally associated with notable improvement in physical, emotional, and social health.